Networks and Netwars The Future of Terror, Crime, and Militancy - Arquilla, John (RAND Corporation, 2001)
Netwar-like cyberwar-describes a new spectrum of conflict that is emerging in the wake of the information revolution. Netwar includes conflicts waged, on the one hand, by terrorists, criminals, gangs, and ethnic extremists; and by civil-society activists (such as cyber activists or WTO protestors) on the other. What distinguishes netwar is the networked organizational structure of its practitioners-with many groups actually being leaderless-and their quickness in coming together in swarming attacks. To confront this new type of conflict, it is crucial for governments, military, and law enforcement to begin networking themselves.